Avaliação isolada e combinada de oxidantes sob radiação UVC visando à degradação simultânea de colchicina, nitazoxanida e sulfametoxazol em efluente sanitário terciário: Otimização por análises multivariadas - Costa, Lucas Gustavo (2024)
The urgent search for treatments for covid-19, combined with public fear, has led to the indiscriminate use of drugs with little or no evidence of efficacy against the disease, increasing the concentration of these substances in wastewater. The efficiency of the degradation of organic microcontaminants (with different chemical structures and characteristics) by advanced oxidation processes depends on the oxidant applied and the preferential reaction of each oxidative radical in the medium. Thus, studies aimed at the simultaneous use of radicals in the degradation of these substances is a way of improving their efficiency. The present work evaluated hydrogen peroxide (H2O2), persulfate (S2O8(2–)) and hypochlorite (OCl–) in isolated or combined form and in different concentrations (0-400 µM) under UVC radiation (254 nm, 8 W), as precursors of highly oxidizing radicals (HO●, Cl● and SO4●–) for the simultaneous degradation of colchicine, nitazoxanide and sulfamethoxazole at a concentration of 325 nM (each drug) in tertiary wastewater, using multivariate optimization tools. Two combinations of oxidants were found to be efficient in degrading the drugs, showing superior performances to the oxidants alone: the first consisted of 240 µM of H2O2 and 240 µM of OCl– and the second of 280 µM of H2O2 and 160 µM of S2O8(2–), achieving degradations of over 92% (LQ ≤ 26 nM) in 30 min for the first and 20 min for the second, while the isolated oxidants achieved degradations of 67 ± 5%, 77 ± 3% and 80 ± 1% respectively for 480 µM OCl–, 440 µM S2O8(2–) and 440 µM H2O2. In addition to the high degradation rates, the two oxidant combinations were effective in reducing the effluent's toxic effects, considering the parameters of phytotoxicity in Lactuca sativa, cytotoxicity and genotoxicity in Allium cepa, and oxidative stress in earthworms (Eisenia andrei). When applied to the actual microcontaminants in the matrix, both processes reduced the load of these substances, helping to improve the quality of the wastewater. These results indicate that the combination of oxidants is an excellent alternative for the degradation of emerging contaminants present in tertiary wastewater and demonstrate] the potential of the processes developed for scale-up and continuous flow studies.